A Pragmatic Introduction to Chaos Theory for Engineers - Montenegro Joo, Javier (2009)
Highly repetitive mechanical systems like those present in industrial machinery, are prone to undergo chaos. To understand this, engineers responsible for the operation of machinery systems, must be aware of the “Routes to Chaos”. This work presents the results of an investigation carried-out in a Virtual Laboratory, created to investigate the transition to chaos in oscillating (rotating) systems, immersed in a dampening medium (impossible to avoid damping in a non ideal situation), under the action of an applied force (a motor).